The Repellent and Attractant Effect for Different Formulations of Pea and soybean seeds and Extracts Against Third Larval Instars of Khapra Beetle Trogoderma granarium Everts - Riyad Ahmed Al-Iraqi; Younis Ibrahim Muhammed Ali Al-bugoary (Tikrit Journal of Pure Science)
This study was conducted to evaluate the effect of crude powders at (0.4 and 0.6)% concentration in addition to petroleum ether, chloroform, ethanol alcohol and water extracts at (0.10 and 0.20)% concentration of pea and soybean seeds against khapra beetle, When these powders and extracts were mixed with wheat grains and rearing the insect on its. The repellent and attractant effect for the powders and extracts were estimated against the third larval instars. Results indicated that the all powders and extracts of pea and soybean seeds showed repellent character to 3rd larval instars of khapra beetle but whit different percent. The pea and soybean powders were superior than extracts for larval repellency which gave percent repellency of (57.21 and 59.80)% respectively with no significant different between them. The alcohol extracts for pea and soybean have the pest repellent effect than other extracts which gave (51.65 and 38.70)% respectively, with significant different between them. Otherwise, the petroleum ether extract for each of pea and soybean showed the less percent repellency which was (6.52 and 24.42)% respectively, but differences in their repellency degree.